PROBLEMS OF THE LEGAL REGULATION OF ACCOUNTABILITY IN THE FIELD OF TAXES AND FEES - A. M. Gogolev (Финансы: теория и практика)
Within the declared perspective the author considered some problematic issues of implementation by offi cials of tax authorities of production on cases of offenses in the fi eld of taxes and fees, for the purpose of development of concrete measures and suggestions for improvement of a legal regulation of a procedural order of consideration of this category of affairs and accountability for violation of the tax law. Thus the author pays attention that feature of purpose of punishments, that some subjects of legal relationship responsible can be made for the same offense in the tax sphere is: the legal entity (as a rule, according to standards of the Tax Code of the Russian Federation), the offi cial or simply natural person (according to standards of the Code of the Russian Federation on Administrative Offences).And in the presence as a part of crime signs — that and natural person (according to the criminal code of Russian Federation).Summarizing the author notes that at identifi cation of the fact of an offense during cameral or exit tax audits for which administrative responsibility is provided, it is expedient to make the protocol on an administrative offense and to transfer him to the offi cial, whose competence includes consideration of this category of affairs within administrative process, along with further implementation of control and supervising production, and on the end of tax audit to draw up the relevant statement. In this connection, new edition of item 15 of Art. 101 and item 13 of Art. 101.4 of the Tax code of the Russian Federation is offered.